Faktor-faktor yang Mempengaruhi Petani dalam Memanfaatkan Program Lumbung Pangan di Desa Danau Karya Kecamatan Anjir Pasar Kabupaten Barito Kuala - Sulaiman Sulaiman; Masyhudah Rosni; Hairi Firmansyah (AGRIDES: Jurnal Agribisnis Perdesaan, 2015)
Public storage is a place or building where a group of farmers store grain or other foodstuffs to anticipate the scarce season, crop failure due to natural disasters and pests/diseases, and the possibility of a temporary shortage. The study is intended to know the level of farmer participation in utilizing the public food food storage, the factors associated with the farmer participation , and excavatethe problems faced by farmers i n participatingPublic Food Storage Program in Dosa Danau Karya, Kecamatan Anjir Pasar,Kabupaten Barito Kuala. The study find s that the level of farmerpartici pation in food stora ge activities can be classified into low level. There is no significant relationship between age, education, experience, and acreage of the farming area with the farmer participation. The most fundamental problem is capital problem, as well as the jealousy of non-member farmer.